AN ANALYSIS OF CODE-SWITCHING USED BY TEACHERS IN TEACHING ENGLISH OF 8TH GRADE STUDENTS IN SMP NEGERI 1 YOGYAKARTA DURING COVID-19 PANDEMIC - Luisa Idana (Jurnal Bahasa Lingua Scientia, 2021)
The aim of this research was to analyze the use of code-switching by the teachers in teaching English to 8th-grade students in SMP Negeri 1 Yogyakarta during an online class in the Covid-19 pandemic. This research was conducted (1) to find the types of code-switching and (2) to identify the functions of code-switching used by the teacher in teaching English to 8th-grade students in SMP Negeri 1 Yogyakarta. This research was a descriptive qualitative research. The techniques of collecting the data were observation, video audio recording, and interview. After gathering the data, the research transcribed and classified the data into the types and functions of code-switching. The result of this research showed that there were three types of code-switching and three functions of code-switching used by the teachers in teaching 8th grade students of class D and G during the online class. Based on the analysis of the data, the dominant type used was inter-sentential switching while the function that was frequently used was repetitive function. Moreover, code-switching was preferred by teachers as an effective medium of teaching specifically in language classes. Code-switching was utilized as a language strategy that helps to facilitate conversation and keeping communication as an ongoing process in the online teaching language during the covid-19 pandemic condition.